Design and implementation of a Smart Measurement System for AMI in the microgrid of the University of Nariño - Arciniegas M., Andrés F.; Imbajoa R., David E.; Revelo F., Javier (Enfoque UTE, 2017)
This project describes a proposed Measure Management System, from the design stage to the implementation of a prototype smart meter, adapted to operate in the microgrid at the University of Nariño. This device features a constant record of measures, with resolution of 24 bits, sufficient to perform power quality analysis. In addition, it is integrated into the SCADA system through the open protocols MODBUS, DNP3 and IEC 61850, with scheduled cybersecurity techniques. Likewise, several management platforms for the monitoring of electrical variables and control over the current flow to the loads is designed. Finally, two study cases show the application of the implemented measure management system in the microgrid.